Obstacles of Accessibility for the Disabled People in the Campus 1 UPGRIS - Baju Arie Wibawa; Kurnia Widiastuti (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2019)
As a public building, the Campus 1 of UPGRIS requires to comply with the accessibility for all (including the diffabled people). Yet, the current condition causes the diffable people unable to access the facilities of the building, which means they are not capable of doing their activities on their own. How should we determine the condition? and how should be advise to retrofit?. The purpose of this reasearch is to identify and analyse the need of diffabled people facilities in campus 1 UPGRIS which have multiple factor. Qualitative and quantitative methods are used in the process of analyzing the problem through comparative analysis according to the regulation, hereinafter a scoring analysis will be held quantitatively to determine the priority of the problem. Commonly the dimension of the doors which width less than 80 cm, so the wheelchair can't go through the room. The conclusion for all building, is not prepared well for the diffable people acting independently.